Alexander Disease Modeling in Zebrafish: An In Vivo System Suitable to Perform Drug Screening - Candiani, Simona (Genes (Basel), 2020)
Alexander disease (AxD) is a rare astrogliopathy caused by heterozygous mutations, either inherited or arising de novo, on the glial fibrillary acid protein (GFAP) gene (17q21). Mutations in the GFAP gene make the protein prone to forming aggregates which, together with heat-shock protein 27 (HSP27), αB-crystallin, ubiquitin, and proteasome, contribute to form Rosenthal fibers causing a toxic effect on the cell. Unfortunately, no pharmacological treatment is available yet, except for symptom reduction therapies, and patients undergo a progressive worsening of the disease. The aim of this study was the production of a zebrafish model for AxD, to have a system suitable for drug screening more complex than cell cultures. To this aim, embryos expressing the human GFAP gene carrying the most severe p.R239C under the control of the zebrafish gfap gene promoter underwent functional validation to assess several features already observed in in vitro and other in vivo models of AxD, such as the localization of mutant GFAP inclusions, the ultrastructural analysis of cells expressing mutant GFAP, the effects of treatments with ceftriaxone, and the heat shock response. Our results confirm that zebrafish is a suitable model both to study the molecular pathogenesis of GFAP mutations and to perform pharmacological screenings, likely useful for the search of therapies for AxD.